An efficient technique for the prediction of solvent-dependent morphology: the COSMIC method - Gale, Julian; Rohl, Andrew (Taylor & Francis Ltd, 2007)
We have developed a method of calculating the solvation energy of a surface based on an implicit solvent model. This new model called COSMIC, is an extension of the established COSMO solvation approach and allows the technique to be applied to systems of any periodicity from finite molecules, through polymers and surfaces, to cavities of water within a bulk unit cell. As well as extending the scope of the COSMO technique, it also improves the numerical stability through removal of anumber of discontinuities in the potential energy surface. The COSMIC model has been applied to barium sulfate, where it was found to produce similar surface energies and configurations to the much more computationally expensive explicit molecular dynamics simulations. The calculated solvated morphology of barium sulfate was found to differ significantly to that calculated in vacuum with a reduced number of faces present.